Exploring the interplay of trunk and shoulder rotation strength: a cross-sport analysis - Hank, Mikulas; Miratsky, Petr; Ford, Kevin R.; Clarup, Christian; Imal, Osman; Verbruggen, Ferdia Fallon; Zahalka, Frantisek; Maly, Tomas (Frontiers in Physiology, 2024)
Trunk and shoulder strength are shown to be involved in performance limitations, as well as contributing to stability, power output, and reducing the risk of injury. Although their biomechanical interaction is a critical aspect for athletes, there is limited research on the relationship between trunk and shoulder strength in sports where upper body mechanics are critical for optimal performance.Purpose: This study examined the differences and relationships between trunk rotational strength and shoulder rotational strength among athletes participating in mixed martial arts (MMA), tennis, swimming, and baseball.Methods: Maximal voluntary contraction tests were performed to evaluate strength of 39 professional adult male athletes from MMA (n = 6), tennis (n = 11), swimming (n = 11) and baseball (n = 11). Peak force data were used in sports comparison and relationship analysis between trunk and shoulder variables.Results: The findings revealed a complex and significant relationship between trunk and shoulder strength, with unique patterns for each discipline. Tennis players exhibited a strong correlation between trunk bilateral differences and internal shoulder rotation, while other disciplines demonstrated a more balanced use of trunk asymmetry. Swimmers displayed the best interactions between trunk and shoulder overall, emphasizing the aquatic environment's biomechanical demands. In MMA, the strongest correlation was between shoulder internal and external rotation with the trunk, mainly due to the number of defensive movements in addition to offensive ones. Baseball pitchers showed a significant correlation between internal/external shoulder rotation strength ratio and trunk asymmetry. Conclusion: While no differences in peak force variables were found, unique relationships between trunk and shoulder rotational performance were discovered. The results suggest a long-term sport-specific adaptation of the trunk-shoulder interaction in sports that require upper limb power movements. It seems, that the relationship between the various parameters of trunk and shoulder was influenced by the movement stereotype of each sport. Therefore, recognition of sport-specific interactions is critical to the development of effective training programs that enhance performance and potentially reduce injury risk in different sports. Researchers and practitioners should focus on longitudinally monitoring fluctuations in TRS and SRS relationships throughout each sport season and examining potential associations with injury incidence.